Message Adaptation Strategies for Culturally Sensitive Maternal Health Communication - Omoloso, Aisha Imam; Ahmad, Mohd Khairie; Ramli, Romlah (2018)
Adaptation of messages to suit the sociocultural characteristics of the audience is one of the doctrines of cultural appropriateness in culture sensitive health communication. However, studies that explicate such message adaptation strategies from the audience perspective are rarely seen in maternal health communication literatures about non-western nations. Therefore, through exploration of cultural and maternal health promotion experiences of women in Nigeria, this study highlights cultural message adaptation strategies, as conceived by the women. The study is a descriptive phenomenological study. Indepth interviews were conducted to collect data from 48 women from 4 major ethnic groups on Nigeria. Participants comprised 30 perinatal women, 9 elders/grandmothers and 9 maternal health experts, selected through snowballing and purposive sampling. Data was analysed by incorporating phenomenological guidelines. Findings revealed message adaptation strategies like local languages and use of media, combined with sociocultural characteristics including use of opinion leaders, diplomatic approach, cultural appreciation, incentives and evidence.